Garuda shrine at Vyankatesh Balaji Temple - Ghosh, Ayan (2023)
The Vyankatesh Balaji Temple has a marble Garuda in a kneeling posture, offering fruit with both hands. However, this image is slightly different from the usual Garuda iconography which is more ferocious. Unlike here, Garuda is usually depicted with a pair of wings and a beaked bird-like nose. Here the Garuda is adorned by Nagas. They coil around the arms, on the waist, and around the ankles. Instead of fighting Garuda, their mortal enemy, the Nagas appear to be paying homage to Lord Balaji in unison.